BCL10 – Bridging CARDs to Immune Activation - Gehring, Torben; Seeholzer, Thomas; Krappmann, Daniel (Frontiers in Immunology, 2018)
Since the B-cell lymphoma/leukemia 10 (BCL10) protein was first described in 1999, numerous studies have elucidated its key functions in channeling adaptive and innate immune signaling downstream of CARMA/caspase-recruitment domain (CARD) scaffold proteins. While T and B cell antigen receptor (TCR/BCR) signaling induces the recruitment of BCL10 bound to mucosa-associated lymphoid tissue (MALT)1 to the lymphocyte-specific CARMA1/CARD11–BCL10–MALT1 (CBM-1) signalosome, alternative CBM complexes utilize different CARMA/CARD scaffolds in distinct innate or inflammatory pathways. BCL10 constitutes the smallest subunit in all CBM signalosomes, containing a 233 amino acid coding for N-terminal CARD as well as a C-terminal Ser/Thr-rich region. BCL10 forms filaments, thereby aggregating into higher-order clusters that mediate and amplify stimulation-induced signals, ultimately leading to MALT1 protease activation and canonical NF-κB and JNK signaling. BCL10 additionally undergoes extensive post-translational regulation involving phosphorylation, ubiquitination, MALT1-catalyzed cleavage, and degradation. Through these feedback and feed-forward events, BCL10 integrates positive and negative regulatory processes that govern the function as well as the dynamic assembly, disassembly, and destruction of CBM complexes. Thus, BCL10 is a critical regulator for activation as well as termination of immune cell signaling, revealing that its role extends far beyond that of a mere linking factor in CBM complexes.